ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN TERHADAP EFEKTIVITAS PENGENDALIAN PIUTANG PADA PT. ASTRA INTERNATIONAL TBK-TSO CABANG KRAKATAU - Sari, Dina Novita; Mulyani, Sri; Sumekar, Aried (Worksheet : Jurnal Akuntansi, 2024)
This research aims to (1) find out how the sales accounting information system in the company (2) find out the problems in the implementation of the sales information accounting system at the company (3) provide input in the processing or design of sales accountancy information system that meets the need for information about the sales in cash or credit in the enterprise. This research was carried out at the Astra International Tbk-Tso branch of Krakatau, located in the northern city of Sumatra during January 2024, the method used was to describe the information system of sales accounting and then describe what problems are in the company, and then look for the problems of the system. From the research and analysis that has been done it can be concluded that: (1) in the PT. Astra international tbk -Tso already there is a simple sales accountancy system (2) problems in PT. The Astra Internationals that arose as a result of the weaknesses of the still ineffective sales accountant system that exists within the company i.e. often sales reports are misrepresented in the recording of sales reports of creditors that have not been properly implemented, difficulties in sales reports. (3) making sales reports through the sales information system that can be expected to meet the needs of the company is the role of the explanation of the sales reports in order to facilitate the dismantling of sales reporting